The effects of personality and age on job satisfaction and job stress - Shasvini Naidu Nagiah,; Lin, Mei-Hua (Penerbit Universiti Kebangsaan Malaysia, 2020)
Past research has found that personality assist us in coping with job stressors and boost performance. In the current study, we aim to examine whether age or personality has a stronger role in predicting job satisfaction and job stress. We proposed that higher agreeableness and older adult will have higher job satisfaction. We also proposed that individuals with higher neuroticism and younger employees will have higher stress with their job. One hundred and thirty-one full time employees (64 males, 67 females) aged between 18 to 65 years old from Malaysia were recruited. Participants completed the Big Five Inventory, Facet Satisfaction Scale, Perceived Stress Scale and demographic form. Findings indicated that higher agreeableness predicted higher job satisfaction while higher neuroticism predicted higher job stress. Personality played a stronger role than age in predicting job satisfaction and job stress. The paper further suggested to research on the impact of personality and age on employee retention rate.